Global governance reform breaking the stalemate - Bradford, Colin I.; Linn, Johannes F. (Brookings Institution Press, 2007)
"Explores a wide range of challenges facing the international community in reforming international institutions and global governance groups. Argues for reform of global governance groups, especially reconstituting the G8, and individual institutional reforms in the IMF, World Bank, and the United Nations and in global health and environmental governance"--Provided by publisher.